The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1111/j.1747-0803.2008.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography and Management of Sick Neonates in the Intensive Care Unit

Abstract: To evaluate the influence of echocardiographic examination in the clinical management of the sick neonate, 241 patients, admitted to the neonatal intensive care unit of a tertiary referral center that had echocardiograms with data available for review, were enrolled in a retrospective study. Asymptomatic murmurs (45%) followed by extracardiac anomalies/dysmorphic features (24%) were the most common clinical indications for requesting an echocardiogram. Congenital structural abnormalities (33%), hemodynamically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…The evidence regarding the impact and safety of echocardiography performed by neonatologists in the NICU setting is largely available in the form of retrospective and prospective descriptive studies (Table 1). 2,5,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] These reports have consistently shown that, when available, targeted neonatal echocardiography is commonly used by neonatal clinicians in a number of cardiorespiratory disorders, often leads to changes in clinical management, Kadivar et al 19 Retrospective study of 241 neonates who underwent echocardiography performed by neonatologists under supervision of pediatric cardiologists at a single tertiary center. Most common clinical indication was murmurs, followed by extracardiac anomalies/dysmorphic features.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence regarding the impact and safety of echocardiography performed by neonatologists in the NICU setting is largely available in the form of retrospective and prospective descriptive studies (Table 1). 2,5,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] These reports have consistently shown that, when available, targeted neonatal echocardiography is commonly used by neonatal clinicians in a number of cardiorespiratory disorders, often leads to changes in clinical management, Kadivar et al 19 Retrospective study of 241 neonates who underwent echocardiography performed by neonatologists under supervision of pediatric cardiologists at a single tertiary center. Most common clinical indication was murmurs, followed by extracardiac anomalies/dysmorphic features.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic and diastolic left ventricular functions are critical determinants of sepsis-induced cardiovascular disorders. 6,7 Many cellular pathways of left ventricular systolic function are impeded during sepsis and implicated in the active relaxation of the left ventricle. 8 In our study, preterm neonates with clinical sepsis had temperature instability, respiratory (grunting, retraction, apnea, tachypnea, or cyanosis), gastrointestinal (feeding intolerance or abdominal distention), neurologic (hypotonia, lethargy, seizures), cardiovascular (bradycardia, tachycardia, poor perfusion, or hypotension), or hematology (thrombocytopenia, prolonged coagulation time, bleeding, or anemia) problems.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates with nonurgent problems are assessed in the daily outpatient clinics, while those with moderately severe clinical problems may need transfer for diagnostic clarification or advice on management. [3]…”
Section: Discussionmentioning
confidence: 99%